Geographical analysis of the ecological tourism components of Al Hammar marshes in southern Iraq - Mohammed A almusawi; Bashar F. Maaroof ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
The Iraqi Marshlands are the largest environmental system of its kind in the Middle East and Western Asia. The area of ​​this vast water swamp is about 16,000 square kilometers. The marshes extend from three southern governorates of Amarah, Nasiriyah and Basra, an integral part of the inter-continental migratory routes, support for endangered species, the continuation of freshwater fishing grounds, and the marine ecosystem of the Gulf, as well as their environmental importance, The Marshlands are an unrivaled human heritage and have been home to indigenous people for thousands of years, Hawr al-Hammar is located south of the Euphrates River and extends from Shuyukh market in the west to the outskirts of Basra at the Shatt al-Arab to the west. The length of the 90 km and width between 25-30 km, and its surface area was about 3000 km 2, the goal of the search to reveal the natural and human characteristics and investment tourism after the planning and development of this environment and relied on a set of maps and images and sources related to the subject of the study and concluded the research into a set of conclusions